Peran Intellectual Capital Disclosure dan Green Culture Dalam Meningkatkan Green Economic Performance - Johannes Kristian Siregar; Antonius Bimo Rentor; Intan Putri Saleha; Anisa Putri Azzahra (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2026)
The increasingly fierce economic competition and uncertain economic conditions post-Covid-19, where manufacturing companies are expected to compete and required to be more transparent in disclosing information about their operations. The decline in the PMI Manufacturing impacts layoffs and affects the decline in public purchasing power, while at the same time, the production of goods will be limited, resulting in a trade deficit. The researchers aim to reveal how Intellectual Capital Disclosure and Green Culture influence Green Economic Performance. There are 142 non-cyclical consumer manufacturing companies in the IDX population, and 27 of those companies are used as samples. Multiple linear regression analysis is the method used to analyze the data. The disclosure of Intellectual Capital has a negative effect, while Green Culture has a positive effect on Green Economic Performance.